Cardiovascular and genitourinary anomalies in patients with duplications within the Williams syndrome critical region: Phenotypic expansion and review of the literature. Issue 8 (20th May 2014) - Zarate, Yuri A.; Lepard, Tiffany; Sellars, Elizabeth; Kaylor, Julie A.; Alfaro, Maria P.; Sailey, Charles; Schaefer, G. Bradley; Collins, R. Thomas
<x xml:space="preserve">Abstract</x> Williams syndrome results from a microdeletion of approximately 1.5 Mb of chromosome 7q11.23. Several patients have been reported with the reciprocal microduplication in association with a variety of phenotypic features including cognitive impairment and typical facial features, though only a few have had birth defects. We report on three probands with duplications within 7q11.23 of variable sizes; two with cardiovascular involvement including aortic dilation and the other with unilateral renal and gonadal agenesis. We offer a comparison with previously reported cases of duplications of 7q11.23. In light of the present cases, we recommend undertaking echocardiographic and renal ultrasound evaluation of patients with documented 7q11.23 duplications. Further, this cytogenetic abnormality should be part of the differential diagnosis for patients with aortic dilation, as well as those with unilateral renal and gonadal agenesis. © 2014 Wiley Periodicals, Inc.